Phosphorus diffusion from a spin-on doped glass (SOD) source during rapid thermal annealing - Mathiot, D.; Lachiq, A.; Slaoui, A.; Noël, S.; Muller, J.C.; Dubois, C. (Materials science in semiconductor processing, 1998)
Limiting thermal exposure time using rapid thermal processing (RTP) has emerged as a promising simplified process for microelectronics applications and for manufacturing of terrestrial solar cells in a continuous way. Especially, rapid thermal diffusion (RTD) of phosphorus from doped oxide films (SOD) was extensively used for the emitter formation purpose but few work concerned the diffusion mechanism. Here we investigate more in details the diffusion kinetics of phosphorus after rapid thermal annealing of P-SOD coated silicon samples. The observed enhanced distribution of phosphorus after RTD is discussed based on the dopant sources and processing conditions. Comparisons between experimental profiles and simulation results using up to date phosphorus diffusion models allow us to discriminate between various possible enhancement mechanisms.